ASSESSING ECOTOURISM POTENTIAL FOR SUSTAINABLE DEVELOPMENT OF COASTAL TOURISM IN QESHM ISLAND, IRAN. - Azam SAFARABADI (European Journal of Geography)
Ecotourism is visiting nature-based attractions, with an emphasis on learning, education, environmental protection and sustainability. Qeshm Island with its unique nature, geological and geomorphological features, and also, ecological-cultural diversity can be regarded as an influential factor in the development of the region's ecotourism. The current descriptiveanalytical study applies the Pralong's method to assess the scientific, economic, cultural and aesthetic value of ecotourism attractions of Qeshm Island. Then, by identifying the attractions of the island and estimating their quantity and quality as the productivity scale, and grading each of these values, a comparison is made in terms of tourism attractions and productivity scale. The results showed that Star valleys scored 0.75 in aesthetic attractiveness, 0.55 in economic and 0.67 in tourism, Hara Marine Forests scored 0.7 in science and 0.52 in tourism, Portuguese Castle scored 0.67 in culture and 0.5 in tourism, and Gold Wells scored 0.41 in tourism.